Biological control of pre-harvest aflatoxin contamination in groundnut (Arachis hypogaea L.) with Bacillus subtilis G1. (2nd April 2016) - Shifa, H.; Tasneem, Shazia; Gopalakrishnan, C.; Velazhahan, R.
Abstract : The antagonistic activity of Bacillus subtilis strain G1 was tested against various isolates of Aspergillus flavus in vitro . A talc-based powder formulation of B. subtilis strain G1 was prepared and evaluated to control A. flavus infection and aflatoxin B1 contamination in groundnut under greenhouse and field conditions. The results showed that B. subtilis strain G1 could inhibit the growth of all isolates of A. flavus tested in dual culture assay and the growth inhibition ranged from 93 to 100%. Results of greenhouse and field experiments indicated that B. subtilis strain G1 when applied to groundnut as seed treatment and soil application significantly suppressed A. flavus population in the soil, A. flavus infection and aflatoxin B1 content in kernels and increased the pod yield. These studies show that B. subtilis strain G1 has potential as a biocontrol agent for control of aflatoxin contamination in groundnut.